2021
DOI: 10.2217/fca-2020-0220
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease in Acute Coronary Syndromes: real-world Data of long-term Outcomes

Abstract: Aim: Patients with chronic kidney disease (CKD) are at increased cardiovascular risk. Methods: Patients with acute coronary syndrome were retrospectively allocated to three groups (stage 3A, stage 3B or stage 4) based on the Kidney Disease Improving Global Outcomes classification formulas: the CKD Epidemiology Collaboration (CKD-EPI; N = 401) and the modification of diet in renal disease (n = 355). The primary end point was all-cause mortality (median follow-up time, 32 months [ 15–70 ]). Results: Study result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, few studies show kidney disease as an indicator of mortality in patients presenting with ACS. Recently, a study found a correlation between CKD and a worse long-term prognosis in ACS [8], although when adjusted for other confounders, the association was not clinically important.…”
Section: Introductionmentioning
confidence: 97%
“…However, few studies show kidney disease as an indicator of mortality in patients presenting with ACS. Recently, a study found a correlation between CKD and a worse long-term prognosis in ACS [8], although when adjusted for other confounders, the association was not clinically important.…”
Section: Introductionmentioning
confidence: 97%